APPLICATION OF THE PROJECT-BASED LEARNING MODEL ON PROKARYOTIC MATERIAL TO IMPROVE COGNITIVE, AFFECTIVE, AND PSYCHOMOTOR LEARNING OUTCOMES OF GRADE - ilmi maehanifa; Atip Nurwahyunani; Praptining Rahayu (BIOMA : Jurnal Ilmiah Biologi, 2026)
This study aimed to determine the effect of the Project-Based Learning (PjBL) model on students' cognitive, affective, and psychomotor learning outcomes in learning prokaryotic material. The research was conducted at SMA Kesatrian 2 Semarang using a quasi-experimental method with a nonequivalent control group design. The final sample consisted of 25 students in the experimental class and 29 students in the control class, selected through purposive sampling. The research instruments included cognitive learning outcome tests, affective observation sheets, and psychomotor observation sheets. Data were analyzed using the Shapiro–Wilk normality test, Levene's homogeneity test, the Mann–Whitney U test, the independent samples t-test, and the N-Gain test. The results showed a significant difference in cognitive learning outcomes (p < 0.001) and affective learning outcomes (p = 0.044) between the experimental and control groups. However, no significant difference was found in psychomotor learning outcomes (p = 0.282). The average N-Gain scores were 0.63 for the experimental group and 0.69 for the control group, both categorized as moderate. Because the two groups differed significantly in their initial abilities before the intervention, the findings should be interpreted with caution.